Difference between revisions of "P. 265, Equation (7.16)"

From Bill Goodwine's Wiki
Jump to navigationJump to search
 
Line 6: Line 6:
  
 
<math>= \lambda^4 - k_4 \lambda^3 + \left( 3 - k_3 \right) \lambda^2 - \left(2 k_4 + k_2 \right) \lambda + \left(1 - k_1 - 2 k_3 \right) = 0.</math>
 
<math>= \lambda^4 - k_4 \lambda^3 + \left( 3 - k_3 \right) \lambda^2 - \left(2 k_4 + k_2 \right) \lambda + \left(1 - k_1 - 2 k_3 \right) = 0.</math>
 +
 +
[[Engineering Differential Equations: Theory and Applications, Springer 2010#Errata|Return to errata.]]

Latest revision as of 14:17, 16 April 2012

The second line should be

The third line should be:

Return to errata.